“MY FAVORITE LITERARY HERO IN THE NOVEL BY A.S. PUSHKIN, EVGENY ONEGIN, TATYANA LARINA” - Yarkulova Fotima Usmanovna; Norkulova Madinabonu Ulugbekovna (Galaxy International Interdisciplinary Research Journal, 2022)
"Eugene Onegin" is a novel in verse by the Russian writer and poet Alexander Sergeevich Pushkin, written in 1823-1830, one of the most significant works of Russian literature. Tatyana Dmitrievna Larina is the main character of the novel. The standard and example for countless female characters in the works of many Russian writers, the "national type" of a Russian woman, passionate and pure, dreamy, straightforward, steadfast friend and heroic wife.